2022
DOI: 10.1007/s11864-022-00989-7
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitors and Chemoradiation for Limited-Stage Small Cell Lung Cancer

Abstract: Opinion statementLimited-stage small cell lung cancer (LS-SCLC) is a potentially curable disease. However, most patients develop disease relapse shortly after definitive treatment. The landmark trials IMpower133 and CASPIAN demonstrated a survival benefit with the addition of immunotherapy to first-line platinum/etoposide for extensive-stage small cell lung cancer. Therefore, it is critical to determine whether advancements in overall survival with immunotherapy can be translated earlier into the treatment par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
(105 reference statements)
1
9
0
Order By: Relevance
“…In the CASPIAN trial, treatment of patients with advanced small cell lung cancer with etoposide plus platinum plus durvalumab resulted in a progression‐free interval of 5.1 months and overall survival of 13.0 months. This shows an overall survival improvement of 2–3 months with the addition of immunotherapy to conventional first line therapy 9,10 . Platinum‐etoposide chemotherapy and concurrent radiotherapy with the addition of durvalumab has been reported to improve overall survival and progression‐free interval 10,11 .…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In the CASPIAN trial, treatment of patients with advanced small cell lung cancer with etoposide plus platinum plus durvalumab resulted in a progression‐free interval of 5.1 months and overall survival of 13.0 months. This shows an overall survival improvement of 2–3 months with the addition of immunotherapy to conventional first line therapy 9,10 . Platinum‐etoposide chemotherapy and concurrent radiotherapy with the addition of durvalumab has been reported to improve overall survival and progression‐free interval 10,11 .…”
Section: Discussionsupporting
confidence: 53%
“…The rationale is the synergistic effect of immunotherapy and radiation. Radiation causes neoantigen release from cancer cells 10,12 . In 1953, Mole observed that after local tumor irradiation, distant nonirradiated sites in the same organism regressed 12 .…”
Section: Discussionmentioning
confidence: 99%
“…For advanced-stage or extensive-stage SCLC, combined chemotherapy (platinum-etoposide) and immunotherapy (atezolizumab or durvalumab during and after chemotherapy) has become the new standard first-line treatment 14. An abundance of preclinical data suggests a synergistic benefit to limited-stage SCLC treated with ICIs and radiation therapy 15. Immunohistochemical staining of neuroendocrine bladder tumours, including SCBC, has shown less expression of Programmed cell Death ligand 1 and density of CD8+ T lymphocyte infiltration 16.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of immunotherapy agents with therapeutic radiation is also being explored in the clinical trial setting in SCLC ( Table 3 ). Radiation causes neoantigen release from cancer cells, and antigen-presenting cells prime T cells to these neoantigens, allowing for T-cell-mediated cytotoxicity of cancer cells 80 ; thus, radiation therapy may potentiate synchronous immunostimulatory and immunosuppressive effects within a tumor site. 81 , 82 However, the phase II STIMULI trial, which examined the use of consolidation nivolumab (1 mg/kg) plus ipilimumab (3 mg/kg) every 3 weeks following primary concurrent chemoradiation (CCRT) therapy did not meet its primary endpoint of PFS benefit, and consolidative ipilimumab with nivolumab was not well tolerated.…”
Section: Novel Immunotherapeutic Approachesmentioning
confidence: 99%